Fundus autofluorescence imaging. (March 2021) - Schmitz-Valckenberg, Steffen; Pfau, Maximilian; Fleckenstein, Monika; Staurenghi, Giovanni; Sparrow, Janet R.; Bindewald-Wittich, Almut; Spaide, Richard F.; Wolf, Sebastian; Sadda, Srinivas R.; Holz, Frank G.
Abstract: Fundus autofluorescence (FAF) imaging is an in vivo imaging method that allows for topographic mapping of naturally or pathologically occurring intrinsic fluorophores of the ocular fundus. The dominant sources are fluorophores accumulating as lipofuscin in lysosomal storage bodies in postmitotic retinal pigment epithelium cells as well as other fluorophores that may occur with disease in the outer retina and subretinal space. Photopigments of the photoreceptor outer segments as well as macular pigment and melanin at the fovea and parafovea may act as filters of the excitation light. FAF imaging has been shown to be useful with regard to understanding of pathophysiological mechanisms, diagnostics, phenotype-genotype correlation, identification of prognostic markers for disease progression, and novel outcome parameters to assess efficacy of interventional strategies in chorio-retinal diseases. More recently, the spectrum of FAF imaging has been expanded with increasing use of green in addition to blue FAF, introduction of spectrally-resolved FAF, near-infrared FAF, quantitative FAF imaging and fluorescence life time imaging (FLIO). This article gives an overview of basic principles, FAF findings in various retinal diseases and an update on recent developments. Highlights: Fundus autofluorescence (FAF) imaging allows for metabolic mapping of the photoreceptor layer and retinal pigment epithelium in-vivo Several sources and confounders of the detected signal should be taken into consideration for the interpretation of FAF image data The application has been expanded with innovations and further developments of imaging systems The clinical application includes macular and retinal degenerations, dystrophies, toxic retinopathies, inflammatory diseases and retinal tumours